Advancements in Nanotechnology for Enhanced Food Safety and Hygiene: Pathogen Detection, Smart Packaging, and Preservation Applications - Awlqadr, Farhang Hameed; Altemimi, Ammar B.; AlKaisy, Qausar Hamed; Qadir, Syamand Ahmed; Faraj, Aryan Mahmood; H.Slih, Tablo Azad; H. Tlay, Rawaa; Abd El-Maksoud, Tarek Gamal Mohamed; Cacciola, Franscesco (Kurdistan Journal of Applied Research, 2024)
Nanotechnology is redefining food safety and hygiene, providing innovative tools to address global challenges. This review delves into the advancements in pathogen detection, smart packaging, and food preservation enabled by nanotechnology. Nanoparticle-based sensors have revolutionized the rapid identification of contaminants like Escherichia coli, Salmonella, and Listeria, offering higher sensitivity and specificity compared to traditional methods. Smart packaging systems equipped with nanomaterials provide real-time contamination alerts and extend shelf life by enhancing barrier and antimicrobial properties. Nanoparticles, such as silver and zinc oxide, are increasingly used in packaging to inhibit microbial growth effectively. Additionally, nanoencapsulation techniques protect bioactive compounds, such as antioxidants and antimicrobials, ensuring their stability and controlled release, which enhances food quality and safety. The emergence of biodegradable nanocomposites and edible films offers eco-friendly packaging alternatives, addressing environmental concerns while maintaining food integrity. Despite these advancements, the high reactivity and small size of nanoparticles raise safety and regulatory challenges, necessitating comprehensive risk assessments and robust frameworks to ensure consumer and environmental protection. This review also explores the potential of utilizing biowaste for green synthesis of nanoparticles, which could further reduce environmental impact. By integrating cutting-edge detection methods, improving packaging solutions, and addressing safety and sustainability challenges, nanotechnology has the potential to transform food safety and hygiene practices. Future research should focus on advancing nanosensor sensitivity, developing sustainable materials, and fostering consumer trust through transparency and education, ensuring a safer and more sustainable food supply chain.